Enterococcus faecalis from Food, Clinical Specimens, and Oral Sites: Prevalence of Virulence Factors in Association with Biofilm Formation - Anderson, Annette C.; Jonas, Daniel; Huber, Ingrid; Karygianni, Lamprini; Wölber, Johan; Hellwig, Elmar; Arweiler, Nicole; Vach, Kirstin; Wittmer, Annette; Al-Ahmad, Ali (Frontiers in Microbiology, 2016)
Enterococci have gained significance as the cause of nosocomial infections, they occur as food contaminants and have also been linked to dental diseases. E. faecalis has a great potential to spread virulence as well as antibiotic resistance genes via horizontal gene transfer. The integration of food-borne enterococci into the oral biofilm in-vivo has been observed. Therefore we investigated the virulence determinants and antibiotic resistance of 97 E. faecalis isolates from the oral cavity, food and clinical specimens. In addition, phenotypic expression of gelatinase and cytolysin were tested, in-vitro biofilm formation was quantified and isolates were compared for strain relatedness via pulsed field gel electrophoresis (PFGE). Each isolate was found to possess two or more virulence genes, most frequently gelE, efaA and asa1. Notably, plaque/saliva isolates possessed the highest abundance of virulence genes, the highest levels of phenotypic gelatinase and hemolysin activity and concurrently a high ability to form biofilm. The presence of asa1 was associated with biofilm formation. The biofilm formation capacity of clinical and plaque/saliva isolates was considerably higher than that of food isolates and they also showed similar antibiotic resistance patterns. These results indicate that the oral cavity can constitute a reservoir for virulent E. faecalis strains possessing antibiotic resistance traits and at the same time distinct biofilm formation capabilities facilitating exchange of genetic material.